The Education of Adolescents. The Final Report and Recommendations of the National Panel on High School and Adolescent Education - Office of Education (DHEW), Washington, DC.; Office of Education (DHEW), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The panel provides an overview of the factors most influential in shaping the American high school as it exists today and recommends (1) replacing the comprehensive high school and providing comprehensive education; (2) establishing participatory education involving adolescents and other interested adults in the community; (3) establishing small, flexible, short-term, part-time, schools; (4) establishing a community guidance center housing the professionals who now work in the high school and other agencies; and (5) reducing compulsory daily attendance from all-day sessions to an academic day of 2-4 hours. These changes are to be accompanied by local testing and evaluation involving adult and adolescent citizen participation. Federal financial support is recommended for research, planning, and evaluation of programs and for the establishment of a national recruitment training and technical support program for operational planning teams to be established at the local level. (Author/MLF)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 ($2.15).
ERIC Note: Table 1 may not reproduce clearly due to small print.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Attendance; Community Involvement; Comprehensive Programs; Educational Change; Educational Improvement; Educational Objectives; Guidance Programs; Nontraditional Education; Part Time Students; School Community Relationship; Secondary Education; Social Change; Reports, Research